Reliable Definition of the Characteristic Strength of Jet Grouted Soils by Random Field Theory. (2016) - Toraldo, Caterina; Modoni, Giuseppe; Croce, Paolo
Abstract: The jet grouted soils are very heterogeneous and thus the statistical methods normally used to define strength of artificial construction materials become extremely conservative. To quantify the mechanical effects of variability on the characteristic strength and the effects of the samples dimensions, the random and spatial variation are firstly explored interpreting field and laboratory tests with the Random Field theory. Then the variability is reproduced on a large volume of material together with the imaginary coring of samples of different sizes and with uniaxial compression testing. This calculation enables to relate the statistical parameters of strength to the size of samples, to the variability observed at small scale and to the correlation distance. The parametrical analysis carried out, has shown that the increase in the element size turns into a reduction of the variability which can be opposed by an increase of the correlation distance.